Contextual Effect of the Integrated Health Post and Social Capital on Completeness of Child Immunization in Pacitan, East Java - Puspita Mayangsari Prabowo; Setyo Sri Rahardjo; Eti Poncorini Pamungkasari (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Around 2-3 million deaths each yearwere caused by diseases that could be pre